Researching the Anglo-Indian Ethnic Minority Community in Odisha-A Methodological Approach - Thomas, Prof. Lyndon D.; Sthitaprajna, Prof. (South Eastern European Journal of Public Health, 2025)
This study explores the lived experiences of the Anglo-Indian community in Odisha, India, using qualitative research methods to capture the complexities of their identities, cultural adaptations, and resistance to marginalization. Employing focus groups, house meetings, and unstructured interviews, the research delves into personal narratives, social dynamics, and cultural patterns within this ethnic minority group. By engaging community members in open, conversational settings, the study uncovers rich, contextual data that goes beyond mere statistical analysis, providing deeper insights into the community's ongoing negotiation of identity amidst societal change. The research challenges stereotypes and aims to present a non-sensationalized, nuanced understanding of the community's reality. Through the application of qualitative techniques, this work contributes to a more empathetic and comprehensive understanding of ethnic minority experiences, emphasizing the fluid and dynamic nature of ethnic identity in the context of post-colonial India. The study also highlights the role of community narratives in fostering social cohesion and activism, particularly in the face of political and social challenges